EKSEKUSI HUKUMAN MATI Tinjauan Maqāṣid al-Sharī’ah dan Keadilan - Imam Yahya (Al-Ahkam, 2013)
The debate about death penalty, is still attracted attention of people. At least, there are, two mainstream firstly those who agrees and secondly who refuses the death penalty being imposed. For those who agrees reasoned that severe violations of the right to life, should be punished by death so that could provide a deterrent effect, while those who refuses argued that the death penalty is a denial of human rights, especially right to life. The essence of the death penalty is not a violation of the law, because the implementation the death penalty actually enforced in order to protect human rights itself. In the view of Islamic law, death penalty, can be done on four cases, namely that of adultery, killing intentionally, Hirabah and apostasy. Furthermore, the death penalty should be carried out in accordance with maqāṣid al-sharī'ah and justice. In maqāṣid al-sharī'ah perspective, the purpose of death penalty should refer to maintain religion (ḥifẓ al-dīn), maintain body or maintain the survival (ḥifẓ al-nafs), mind (ḥifẓ al-'aql), descent (ḥifẓ alnasl), and maintaining property (ḥifẓ al-māl). While in the perspective of justice, State, on behalf of the law must protect its citizens from legal events that harm society.